Combating money laundering in Malaysia : current practice, challenges and suggestions - Amirah Mohamad Abdul Latif,; Aisyah Abdul-Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Money laundering is a global threat to financial institutions especially the banking industry since it may weaken and expose the institutions to serious risks such as operational, legal and reputational risks. Against this background, the objectives of the study are to analyse the current practice on the prevention of money laundering in selected banks in Malaysia, to investigate the barriers to the implementation of effective Anti-Money Laundering (AML) regulations and to identify the ways to improve the implementation of AML in Malaysia. The study was conducted using qualitative method via interviews with 6 respondents from 6 Islamic & Conventional banks in Malaysia. The preliminary findings showed that the banking institutions’ current practice is fully complying with AML regulations under the AMLA 2001. The findings also demonstrated that the barriers to effective implementation of AML regulations are in line with those of previous study, which are lack of expert staff as the top factor together with an additional factor, which is lack of customers’ education and awareness on money laundering. Hence, to improve the implementation of AML in Malaysia, this study suggested to firstly strengthen the collaboration with government and relevant authorities to ensure strong enforcement action is taken against the criminals. Secondly, collaboration of BNM with banks and local media to increase public awareness and education on financial crime. Thirdly, to invest on employee training, upgrading system management as well as sufficient resources in compliance unit and finally to intensify the “Three Lines of Defence” in Bank Risk Management.